Public Opinion into a New Music Curriculum: a Case Study of Lower-Northern Thailand - Amaro, Tat; Yongnoo, Waraporn (Journal of Fine and Applied Arts Khon Kaen University, 2023)
The thriving of music curriculum development in higher education is contingent upon the shrewdness of curriculum committee. They are responsible for a music curriculum to thrive concurrently with global mainstream by which one of key indicators of success is to meet stakeholders’ expectations. This article aimed at garnering and analyzing public opinion in order to shape a new music curriculum. After distributing and collecting a thoroughly created online questionaire to elicit public opinion from high school students, current music students, music alumni, acclaimed music educators, employers, and others, I used Pivot Table to conduct data analysis that the process resulted in a form of statistics. Then, the data were later translated into descriptions. The results show that there are agreements and arguments on particular subjects amongst those respondents: collective opinions versus branched opinions, as well as some public opinions that do not concur with academics’ propositions.